(15-9)*5= 30
The answer is 30
I can't see what expressions you had posted. Maybe you didn't typed it out, but 649*36=23364
Y - y1 = m(x - x1)
slope(m) = 6/7
(-9,6)....x1 = -9 and y1 = 6
now we sub...pay close attention to ur signs
y - 6 = 6/7(x - (-9)....not done yet
y - 6 = 6/7(x + 9) <===
Answer:
8.49
Step-by-step explanation:
there is a little formula related to the famous formula of Pythagoras.
it says that the height of a triangle is the square root of the product of both segments of the baseline (the segments the height splits the baseline into).
so, x is actuality the height of the triangle.
x = sqrt(3×24) = sqrt(72) = 8.49
Answer:
58
Step-by-step explanation:
58.58 - 0.58 = 58